The Use of Date Juice and Sugarcane Juice for Hypoglycemia Therapy in Young Adult - Hidayati, Nur; Larasati, Fieka Phedy; Rokhman, Abdul (Critical Medical and Surgical Nursing Journal, 2025)
Introduction: Hypoglycemia is a medical emergency requiring immediate intervention as it can lead to fatalities. One of the initial treatments for hypoglycemia out of hospital settings is the administration of sweet food and drinks. This research aims to analyze the difference in blood glucose level increase between respondents given date juice and those given sugarcane juice.  Methods: A quasi-experimental two-group pretest-posttest design was conducted in March 2024, involving 92 students divided into 2 groups (Intervention Group: 46; Control Group: 46) recruited through purposive sampling. Both groups were asked to fast for 14 hours, followed by blood glucose measurement (pretest), and then given date juice (intervention group) and sugarcane juice (control group). Blood glucose post-test was conducted at 15 and 30 minutes after intervention with a glucometer, and data were analyzed using ANOVA (α≤0.05).  Results: The study indicated an increase in blood glucose levels after date juice intake at 15 minutes with a mean of 129.83 mg/dl (p=0.000), followed by a decrease in mean blood glucose from 15 to 30 minutes by 21.7. There was an increase in blood glucose levels after sugarcane juice intake at 15 minutes with a mean of 131.17 mg/dl, followed by a decrease in mean blood glucose from 15 to 30 minutes by 19.8. Statistically, there was no difference in blood glucose increase between the two groups at both 15 minutes (p=0.633) and 30 minutes (p=0.347). Conclusion: Date juice and sugarcane juice similarly increase blood glucose levels and can be used as out-of-hospital therapies for conscious hypoglycemic patients.